Formulation, characterization and evaluation of the effect of polymer concentration on the release behavior of insulin-loaded Eudragit®-entrapped mucoadhesive microspheres - C. Kenechukwu, Franklin; A. Momoh, Mumuni (International Journal of Pharmaceutical Investigation)
Introduction: The aim of this study was to use Eudragit® RL 100 (pH-independent polymer) and magnesium stearate (a hydrophobic droplet stabilizer) in combination to improve the controlled release effect of insulin-loaded Eudragit® entrapped microspheres prepared by the emulsification-coacervation technique. Materials and Methods: Mucoadhesive insulin-loaded microspheres containing magnesium stearate and varying proportions of Eudragit® RL 100 were prepared by the emulsification-coacervation technique and evaluated for thermal properties, physicochemical performance, and in vitro dissolution in acidic and subsequently basic media. Results: Stable, spherical, brownish, discrete, free flowing and mucoadhesive insulin-loaded microspheres with size range of 14.20 ± 0.30-19.80 ± 0.60 µm and loading efficiency of 74.55 ± 1.05-75.90 ± 1.94% were formed. After 3 h, microspheres prepared with insulin: Eudragit® RL 100 ratios of 1:4, 1:6, and 1:8 released 73.40 ± 1.38, 66.20 ± 1.59, and 71.30 ± 1.27 (%) of insulin, respectively. Conclusion: The physicochemical and physico-technical properties of the microspheres developed in this study demonstrated the effectiveness of the Eudragit® RL entrapped mucoadhesive microspheres (prepared by the emulsification-coacervation technique using varying polymer concentration) as a carrier system for oral insulin delivery.
Keywords: Eudragit® RL 100; insulin release; microspheres; percentage mucoadhesion